Translator Education in Times Of Change: Competences, Technologies, and Market Expectations - Mazur, Olena; Naniak, Yuliia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
This study provides a comprehensive analysis of the current state of specialized translation and interpreting training in Ukraine, examining curriculum design, depth of specialization, integration of digital and translation technologies, and alignment with evolving professional market demands. The objective is to identify and characterize the gap between university-based preparation and actual labor market requirements by exploring students’ evaluations of course relevance, satisfaction with their training, and self-assessed readiness for professional practice. The empirical basis is a stratified anonymous survey of 226 undergraduate and graduate students from six Ukrainian universities. A mixed-methods research design was applied to detect correlations between program characteristics and satisfaction indicators. The results show that higher satisfaction levels are associated with increased specialization, practical orientation, and opportunities for authentic project work; however, the findings also reveal insufficient coverage of domain-specific subjects, limited exposure to CAT tools, artificial intelligence applications, business and legal aspects, as well as a lack of systematic career guidance. Respondents express demand for enhanced training in community and conference interpreting, audiovisual translation and localization, and the development of soft skills. The study’s findings support the idea of adapting curricula to align with international competence frameworks, fostering closer cooperation between universities and employers, balancing theoretical knowledge with practical skills, and using student-centered teaching methods to boost graduate competitiveness.